Relationships between vitamin D and iron status in male and female athletes - Malczewska-Lenczowska, J.; Orysiak, J.; Szczepanska, B.; Surala, O.; Sitkowski, D.; Witek, K. (International Journal of Sport Nutrition and Exercise Metabolism, 2017)
Recent evidence suggests that vitamin D may affect iron regulation and erythropoiesis by its influence on hepcidin as well as on erythroid precursors. For these reasons deficit of vitamin D may deteriorate iron status and increase the risk of anaemia. We aimed to investigate whether vitamin D deficiencies have an impact on iron status in normal and iron-deficient athletes. The study included 290 healthy subjects (175 males and 115 females), aged 15-34 years, representing volleyball, cycling, canoeing, rowing, hockey, taekwondo and badminton. Blood for analysis was withdrawn in different seasons.